A Visual-Based Energy Efficient Digital Agro (EE i-Agro) Project for Design & Technology Subject, Based on Computational Thinking Skills Across STEM - Zaman H.B.; Ismail R.; Ibrahim N.; Mohamad U.H. (Springer Science and Business Media Deutschland GmbH, 2025)
Computational Thinking (CT) is a concept used as a systemtic way of thinking and in problem-solving process, not just for computer science but other domains of knowledge. Various research conducted at high school and tertiary levels of education has shown that CT integrated into lessons across STEM have shown positive results. This study conducted at elementary school integrates CT with the Design and Technology (RBT) subject particularly in the Visual-Based Project Production Package Model (VB-P3) across STEM, using computational thinking skills, in the Energy Efficient i-Agro Reservoir Crop System (EE i-Agro) project production process for the Design and Technology (RBT) subject in primary schools. This package is aimed at improving students? problem-solving and thinking skills by making them more creative and innovative. The VB-P3 also includes the development of RBT Energy Efficient i-Agro learning model and modules (EEi-Agro LMM). The VB-P3 model was based on the ?prototyping? iterative model comprising of five (5) main phases; namely analysis, design, development, implementation, and evaluation with appropriate iteration. This model is also based on the COMEL learning model with attributes such as interactivity, fun learning, engaging and motivating, which helps students? learning, with additional components and elements. Hence, this paper highlights the evaluation of the Visual-Based Project Production Package Development (VB-P3) model to develop the Energy Efficient i-Agro Reservoir Crop System (EE i-Agro) Project which can improve thinking and problem-solving skills, to prepare students for the new learning environment and instill sustainability practices in students facing energy transition, climate change and global warming experienced globally. ? The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.